3D-printed multimaterial composites tailored for compliancy and strain recovery. (15th January 2018) - Mansouri, M.R.; Montazerian, H.; Schmauder, S.; Kadkhodapour, J.
Graphical abstract: Abstracts: Co-continuous multimaterial composites are novel types of multifunctional structures. This study focuses on numerical and experimental investigation of the mechanical behavior of 3D periodic single-material cellular D-structure and the corresponding co-continuous composite. Different volume fractions of desired geometry were fabricated by multimaterial fused deposition modeling (FDM) technology and compressive mechanical properties of the samples were obtained by mechanical tests. It was observed that embedding a hyperelastic material to the cellular structure dramatically hindered the shearing bands in localized regions to develop, thereby made it feasible for composite material to undergo larger deformations without failure. Furthermore, it was demonstrated that the soft phase in multimaterial composite induces a homogeneous deformation to cellular structure, which enhances the load-bearing capacity and flexibility of the whole composite. In this paper, it was shown that the co-continuous multimaterial composite provides a well-balanced approach between desired flexibility and load-bearing which is referred to as compliancy. A strain recovery between 82 and 93% was also measured when unloading for multimaterial composite. These integrated properties could be valuable to various engineering applications such as synthetic limbs, soft robotics, and wearable structures as shoes and splints.